Is starting with the feet out of the water faster in backstroke swimming? - Nguyen, C.; Bradshaw, E. J.; Pease, D.; Wilson, C. (Sports Biomechanics, 2014)
This study aimed to determine if starting with the feet above the water (FAW) in male backstroke swimming resulted in faster start times (15-m time) than when the feet were underwater (FUW). It was hypothesised that setting higher on the wall would generate increased horizontal force and velocity, resulting in quicker starts. Twelve high-level male backstrokers performed three trials of the FAW and FUW techniques. A biomechanical swimming testing system comprising one force plate (1,000 Hz), four lateral-view (100 Hz), and five overhead (50 Hz) video cameras captured the swimmers' performance. Data for each participant's fastest trial for each technique were collated, grouped, and statistically analysed. Analysis included Wilcoxon, Spearman Rho correlation, and regression analysis. Wilcoxon results revealed a significantly faster start time for the FAW technique (p < 0.01). Peak horizontal force was significantly smaller for FAW (p = 0.02), while take-off horizontal velocity was significantly greater (p = 0.01). Regression analysis indicated take-off horizontal velocity to be a good predictor of start time for both techniques, and the horizontal displacement of the centre of mass for the FAW start.